Answer: 5.9 cm for both triangles.
Step-by-step explanation:
Hi, since the situation forms 2 right triangles we have to apply the Pythagorean Theorem:
c^2 = a^2 + b^2
Where c is the hypotenuse of a triangle (the longest side of the triangle) and a and b are the other sides.
Replacing with the values given:
c^2 = 3^2 + 5^2
c^2 = 9+25
c^2 = 34
c = √34
c = 5.9 cm
Since both triangles are identical ( same side lengths) the hypotenuse is the same for both, 5.9 cm.
Feel free to ask for more if needed or if you did not understand something.
Answer:
6 is a answer
Step-by-step explanation:
if it is x 3+3 is equal to 6
if it is 10+10 is equal to 20
By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
<h3>How to find the inverse of a function</h3>
In this question we have a <em>rational</em> function f(x) and finding its inverse consists in clearing x in terms of f(x). Prior any algebraic handling, we need to apply the following substitutions:
![x \to y](https://tex.z-dn.net/?f=x%20%5Cto%20y)
![f(x) \to x](https://tex.z-dn.net/?f=f%28x%29%20%5Cto%20x)
![x = \frac{-2\cdot y + 2}{y+7}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-2%5Ccdot%20y%20%2B%202%7D%7By%2B7%7D)
x · (y + 7) = - 2 · y + 2
x · y + 7 · x = - 2 · y + 2
2 · y + x · y = - 7 · x + 2
y · (2 + x) = - 7 · x + 2
![g(x) = \frac{- 7\cdot x + 2}{x + 2}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%5Cfrac%7B-%207%5Ccdot%20x%20%2B%202%7D%7Bx%20%2B%202%7D)
By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
To learn more on inverses: brainly.com/question/7181576
#SPJ1
Answer:
33^2
Step-by-step explanation:
3 x 5= 15
15+18=33
33^2 because there is two triangles your adding to get the answer
Answer:
Step-by-step explanation:
8.5*7.5 = 63.75